PROTECTION OF FOREIGN DIRECT INVESTMENT IN RELATION TO THE APPLICATION OF FAIR AND EQUITABLE TREATMENT PRINCIPLE IN INDONESIA - Syarifah Taskia Az-Zahra; Azhari Yahya (Universitas Syiah Kuala, 2022)
This paper aims to find out the arrangements regarding the protection of foreign direct investment and the consistency between the arrangements contained in the rules against the fair and equitable treatment principle in Indonesia. This study used normative legal research, and found that the regulatory policy regarding the protection of foreign direct investment in Indonesia as stated in article 6 of law number 25 of 2007 concerning investment is not in accordance to fair and equitable treatment principle. The Indonesian government must pour out matters related to transparency and the absence of overlapping rules so as to create better protection by providing clear legal certainty to investors.